Four new Scopalina from Southern California: the first Scopalinida (Porifera: Demospongiae) from the temperate Eastern Pacific - Turner, Thomas L. (Zootaxa, 2021)
Sponges (phylum Porifera) are common inhabitants of kelp forest ecosystems in California, but their diversity and ecological importance are poorly characterized in this biome. Here I use freshly collected samples to describe the diversity of the order Scopalinida in California. Though previously unknown in the region, four new species are described here: Scopalina nausicae sp. nov., S. kuyamu sp. nov., S. goletensis sp. nov., and S. jali sp. nov.. These discoveries illustrate the considerable uncharacterized sponge diversity remaining in California kelp forests, and the utility of SCUBA-based collection to improve our understanding of this diversity.